DEVELOPING DIGITAL SKILLS OF PERSONNEL FOR BECOMING A DIGITAL ORGANIZATION - Jendee, Somrak; คีรีวรรณ์, จุฑารัตน์; Winthachai, Pharadee; Vinijkul, Russadakorn (Journal of MCU Phetchaburi Review, 2026)
This academic article presents guidelines for developing digital skills for government personnel in an era of societal transition from an analogue society to a fully digital one. Therefore, government personnel must be developed and adapted appropriately. Emphasis is placed on developing higher skills to enhance efficiency in traditional work practices and learning new skills to ensure readiness for future changes. A personnel skills development plan includes organizing training and developing the agency's personnel capabilities, both through e-learning and on-site practical training. This includes promoting higher education, hands-on work, self-learning via electronic media, job rotation, knowledge transfer, on-the-job coaching, and the application of technological skills, data analysis, and new technology applications. Online learning targets five groups: newly hired personnel, experienced personnel, supervisors, incumbents, and personnel in various positions. This aims to enable them to utilize digital technology in their work, aligning with Thailand is digital government strategy.